Angiosarcomas of the Bilateral Breast and Heart: Which One is the Primary Site? - Kim, Eun Kyoung (The Korean Association of Internal Medicine, 2012)
A 29-year-old pregnant woman with recurrent pericardial effusion and a cardiac tumor, diagnosed as an angiosarcoma, was treated with surgical resection of the tumor followed by radiotherapy. Immediately after completion of radiotherapy, she developed bilateral breast masses, which were also confirmed as angiosarcomas. We thought this might be the first case of bilateral angiosarcoma of the breast metastasizing to heart mimicking a primary cardiac angiosarcoma, although we could not conclude with certainty that angiosarcoma of the heart was not the primary site.